2009
DOI: 10.1007/s11192-009-0090-2
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing knowledge diffusion of Nanoscience & Nanotechnology by citation analysis

Abstract: This study investigates the knowledge diffusion patterns of Nanoscience & Nanotechnology (N&N) by analyzing the overall research interactions between N&N and nano-related subjects through citation analysis. Three perspectives were investigated to achieve this purpose. Firstly, the overall research interactions were analyzed to identify the dominant driving forces in advancing the development of N&N. Secondly, the knowledge diffusion intensity between N&N and nano-related subjects was investigated to determine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 46 publications
0
14
0
Order By: Relevance
“…On the other hand, critics of the silo argument have demonstrated that researchers constantly import and export ideas across disciplinary boundaries (Jacobs 2014;Jacobs and Frickel 2009). An enormous volume of bibliometric evidence supports this position, from maps of science highlighting connections within and across disciplines (Boyack, Klavans, and Börner 2005;Börner, Chen, and Boyack 2003;Börner et al 2012;Chen and Hicks 2004;Leydesdorff and Rafols 2009;Moody and Light 2006;Skupin, Biberstine, and Börner 2013) to quantitative research on diffusion, collaboration, and the exponential growth of science (Coccia and Bozeman 2016;Coccia and Wang 2016;Crane 1972;Liu et al 2015;Price 1963;Yu et al 2010;Zhu and Yan 2015). Theories, measures, and models of disciplinary knowledge diffusion (Bettencourt et al 2008;Gao and Guan 2011;Herrera, Roberts, and Gulbahce 2010;Vitanov and Ausloos 2012;Yan 2014;Yan et al 2013) and interdisciplinarity (Chen et al 2014(Chen et al , 2015Cronin and Sugimoto 2014;Larivière et al 2014;Light and Adams 2016) are increasingly common.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, critics of the silo argument have demonstrated that researchers constantly import and export ideas across disciplinary boundaries (Jacobs 2014;Jacobs and Frickel 2009). An enormous volume of bibliometric evidence supports this position, from maps of science highlighting connections within and across disciplines (Boyack, Klavans, and Börner 2005;Börner, Chen, and Boyack 2003;Börner et al 2012;Chen and Hicks 2004;Leydesdorff and Rafols 2009;Moody and Light 2006;Skupin, Biberstine, and Börner 2013) to quantitative research on diffusion, collaboration, and the exponential growth of science (Coccia and Bozeman 2016;Coccia and Wang 2016;Crane 1972;Liu et al 2015;Price 1963;Yu et al 2010;Zhu and Yan 2015). Theories, measures, and models of disciplinary knowledge diffusion (Bettencourt et al 2008;Gao and Guan 2011;Herrera, Roberts, and Gulbahce 2010;Vitanov and Ausloos 2012;Yan 2014;Yan et al 2013) and interdisciplinarity (Chen et al 2014(Chen et al , 2015Cronin and Sugimoto 2014;Larivière et al 2014;Light and Adams 2016) are increasingly common.…”
Section: Introductionmentioning
confidence: 99%
“…2: for disciplines such as biology, medicine and economics, the two values differ greatly, while for psychology and biochemistry, they do not. 4 As many bibliometric indices are especially sensitive to highly successful articles (e.g., total number of citations, average number of citations per paper, journal impact factors), understanding the dynamics of highly cited articles is also important in order to better understand the potential drawbacks associated with the use of these indices. In Fig.…”
Section: Life-cycle Of Scholarly Articles Across Fields Of Researchmentioning
confidence: 99%
“…policymaking, as it is considered to be a key driver of economic growth and prosperity [1,2,3]. When the area of knowledge under consideration is narrowed to that of scientific knowledge, interest is usually centered on its flow within and between scientific areas, which is traced through citations in scientific publications [4,5,6]. In this sense, citations serve to document the collective and cumulative nature of knowledge production [7].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Patent citation analyses have found that knowledge embedded in public research patents tends to diffuse more quickly than knowledge embedded in corporate patents (Bacchiocchi and Montobbio 2009). Similar studies also find that the knowledge diffusion process is asymmetric in that it tends to occur more rapidly within, than between, fields (Yu et al 2010). However, a 2010 study suggests that a number of research areas are converging, and the diffusion of knowledge across fields is a major force facilitating this process (Liu and Rousseau 2010).…”
Section: Introductionmentioning
confidence: 96%